Relations of Behavioural Inhibition with Shyness and Social Competence in Chinese Children: Moderating Effects of Maternal Parenting. Issue 3 (6th March 2014) - Chen, Xinyin; Zhang, Guangzhen; Liang, Zongbao; Zhao, Siman; Way, Niobe; Yoshikawa, Hirokazu; Deng, Huihua; Schmidt, Louis A.; Coplan, Robert J.
<x xml:space="preserve">Abstract</x> The purpose of the study was to examine how behavioural inhibition was associated with shyness and social competence and how maternal parenting moderated the associations in urban Chinese children. Participants were 2‐year‐old toddlers (N = 286, 143 boys and 143 girls) and their mothers in P. R. China. Data on behavioural inhibition were collected from laboratory observations. Mothers completed measures of parenting and child shyness and competence. It was found that behavioural inhibition was positively associated with shyness and negatively associated with social competence for children with low maternal support, but not for children with high maternal support, suggesting that maternal support might serve as a protective factor that buffered against the maladaptive development of inhibited children. The results indicate the functional meaning of early childhood inhibition and the role of parenting in today's urban China. Copyright © 2014 John Wiley & Sons, Ltd.